2014
DOI: 10.1002/psc.2730
|View full text |Cite
|
Sign up to set email alerts
|

Concentration-dependent and surface-assisted self-assembly properties of a bioactive estrogen receptor α-derived peptide

Abstract: We have synthesized a 17-mer peptide (ERα17p) that is issued from the hinge region of the estrogen receptor α and which activates the proliferation of breast carcinoma cells in steroid-deprived conditions. In the present paper, we show that at a concentration of ~50 μM, it rapidly forms amyloid-like fibrils with the assistance of electrostatic interactions and that at higher concentrations, it spontaneously forms a hydrogel. By using biophysical, spectral and rheological techniques, we have explored the struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 59 publications
0
27
0
Order By: Relevance
“…Moreover, the recent application of new AFM-based methodologies, such as quantitative nanomechanical mapping and infrared nanospectroscopy, represents a fruitful avenue to unravel the process of monomer misfolding and to elucidate the molecular mechanisms of amyloid polymorphism and formation. The combination of these AFM-based methodologies enables to correlate at the nanoscale the morphological, mechanical and structural properties of amyloids at the individual aggregate scale [12, 61, 137-139]. …”
Section: Single Molecule Investigation By Atomic Force Microscopy Tecmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the recent application of new AFM-based methodologies, such as quantitative nanomechanical mapping and infrared nanospectroscopy, represents a fruitful avenue to unravel the process of monomer misfolding and to elucidate the molecular mechanisms of amyloid polymorphism and formation. The combination of these AFM-based methodologies enables to correlate at the nanoscale the morphological, mechanical and structural properties of amyloids at the individual aggregate scale [12, 61, 137-139]. …”
Section: Single Molecule Investigation By Atomic Force Microscopy Tecmentioning
confidence: 99%
“…Thus, the comparison of the spatially localized IR spectra showed a net variation of the amide I mode conformation from the monomeric to fibrillar state, which well correlated with a random coil to β-sheet transition [214]. A subsequent study aimed to apply AFM-IR exploiting polarized light to demonstrate the amyloidogenic nature of the Erα17p peptide of the estrogen receptor α (ERα) [137]. This receptor is involved in breast cancer and it has been found that it can quickly form hydrogels, which are receiving increasing attention due to their possible use in several medical related applications, such as drug delivery, immobilized antimicrobial surfaces and tissue engineering.…”
Section: Single Molecule Investigation By Atomic Force Microscopy Tecmentioning
confidence: 99%
“…2h). This polarization effect demonstrates that the structure of the fibre is anisotropically ordered and that there are more intermolecular β-sheets oriented perpendicular to the fibre axis 22 . We next performed scanning electron microscopy (SEM) to characterize the structural morphology of the FUS phases.…”
Section: Figurementioning
confidence: 90%
“…A silicon gold coated PR-EX-nIR2 (Anasys, USA) cantilever with a nominal radius of 30 nm and an elastic constant of about 0.2 N m -1 was used. To study polarisation effects, the IR light was polarized parallel and perpendicular the surface of deposition 22 . All images were acquired with a resolution of at least 500×500 pixels per line.…”
Section: Methodsmentioning
confidence: 99%
“…1c). [24][25][26][27][28][29][30][31][32][33][34] AFM-IR is becoming widely applicable in biology since is capable of acquiring simultaneously morphological, nanomechanical and nanoscale-resolved chemical IR maps and absorption spectra from protein aggregates, liquid-liquid phase separated condensates, chromosomes, and single cells. 29,31,[34][35][36] As fundamental achievement, we have recently demonstrated that AFM-IR enables to acquire infrared absorption spectra for secondary structure determination from single protein molecules.…”
mentioning
confidence: 99%